2021
DOI: 10.3390/jcm10112432
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Moderate-Intensity Aerobic Water Exercise during Pregnancy on Quality of Life and Postpartum Depression: A Multi-Center, Randomized Controlled Trial

Abstract: Background: The global prevalence of postpartum depression is about 20%. This disease has serious consequences for women, their infants, and their families. The aim of this randomized clinical trial was to analyze the effectiveness and safety of a moderate-intensity aerobic water exercise program on postpartum depression, sleep problems, and quality of life in women at one month after delivery. Methods: This was a multi-center, parallel, randomized, evaluator blinded, controlled trial in a primary care setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…After excluding duplicated literature, there were 1,300 studies in the analysis, and 52 studies remained after screening the title and abstract. Finally, 20 studies ( Cochrane Library, 1966 ; Armstrong and Edwards, 2004 ; Daley et al, 2008 , 2015 ; Heh et al, 2008 ; Robichaud, 2009 ; Norman et al, 2010 ; Robledo-Colonia et al, 2012 ; Songøygard et al, 2012 ; Haruna et al, 2013 ; Buttner et al, 2015 ; Davis et al, 2015 ; El-Rafie et al, 2016 ; Shelton, 2016 ; Coll et al, 2019 ; Vargas-Terrones et al, 2019 ; Özkan et al, 2020 ; Navas et al, 2021 ; Teychenne et al, 2021 ) were eligible in this systematic review and performed meta-analysis after full-text review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding duplicated literature, there were 1,300 studies in the analysis, and 52 studies remained after screening the title and abstract. Finally, 20 studies ( Cochrane Library, 1966 ; Armstrong and Edwards, 2004 ; Daley et al, 2008 , 2015 ; Heh et al, 2008 ; Robichaud, 2009 ; Norman et al, 2010 ; Robledo-Colonia et al, 2012 ; Songøygard et al, 2012 ; Haruna et al, 2013 ; Buttner et al, 2015 ; Davis et al, 2015 ; El-Rafie et al, 2016 ; Shelton, 2016 ; Coll et al, 2019 ; Vargas-Terrones et al, 2019 ; Özkan et al, 2020 ; Navas et al, 2021 ; Teychenne et al, 2021 ) were eligible in this systematic review and performed meta-analysis after full-text review.…”
Section: Resultsmentioning
confidence: 99%
“…This result also agreed with one previous research that recommended 30–60 min of exercise three times a week ( Dipietro et al, 2019 ). Different intensities of exercise may influence the optimal effects ( Navas et al, 2021 ), and another study even suggested that the higher the intensity of physical exercise, the greater relief of depressive symptoms ( Davenport et al, 2018 ). Sustained high-intensity exercise can significantly increase VO2 max during pregnancy, and pregnant women were also encouraged to engage in moderate-intensity exercise regardless of their previous exercise habits ( Dipietro et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Carolina de Vargas Nunes Coll et al (2019), aerobic and endurance exercise for 16 weeks did not have a significant effect on maternal postpartum depression [22]. Meanwhile, the study by Araceli Navas et al (2021) in Spain that used an intervention in the form of aquatic aerobic exercise stated that the intervention group did not report postpartum anxiety or depression [23]. In a study conducted by Kristian M Songoygard et al (2011) who was guided by a physiotherapist for 12 weeks stated that there was no significant difference according to the respondents' EPDS scores [24].…”
Section: Types Of Exercise In Baby Blues Syndromementioning
confidence: 99%
“…[19] Several modalities, such as psychotherapy, lifestyle changes, exercise, or a combination of these, have been reported to manage this condition. [2–25] However, all of them had limited effectiveness. Fortunately, goal-oriented nursing intervention (GONI) has potential effects for PPD management.…”
Section: Introductionmentioning
confidence: 99%